E-LKPD Berbasis STEAM Dengan Teknologi Augmented Reality (AR) : Upaya Melatih Berpikir Kreatif - Reza Lika Sari; Antomi Saregar; Sodikin (Universitas Hamzanwadi, 2024)
T This research aims to develop and convey the feasibility and user response to E-LKPD assisted by the Augmented Reality (AR) application with a STEAM approach to train creative thinking skills (creative thinking) of class XII students. The research uses the Research and Development (R&D) method with the development of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of material validation by 3 expert validators, media validation by 3 expert validators, teacher responses by 2 educators, and student responses by 68 class XII students at SMA 2 Perintis Bandar Lampung and SMAN 01 Tanjung Raya Mesuji Lampung. Validation results by material and media experts show a very high level of feasibility, with percentages of 89% and 86% respectively. The response from educators and students was also very positive regarding the attractiveness and feasibility of the E-LKPD being developed, with trial results reaching 91% for educators, 88% for small group trials, and 86% for field trials. Based on these results, it can be concluded that the development of AR-assisted E-LKPD with a STEAM approach is declared feasible and interesting as physics teaching material in class XII.